DEVELOPMENT THE VALIDATION OF INDONESIAN VERSION OF SF-36 QUESTIONNAIRE IN CANCER DISEASE - Dyah Ariani Perwitasari (Indonesian Journal of Pharmacy, 2012)
A  Cancer  patients  need  long  term  therapy  in  the  treatment of their disease. One of the outcome of cancer treatment in patients of  quality  of  life.  Because  of  the  limited  instrument  for  measuring cancer patients’ quality of life in Indonesian version, thus this study is  aimed  to  develop  the  validation  of  Indonesian  version  of  Short Form-36  questionnaire  in  cancer  patients.  The  observational  study was  carried  out  in  this  study.  Data  were  collected  from  cancer patients  in  the  Oncology  Department  of   Sardjito  Hospital, Yogyakarta,  Indonesia,  who  were  treated  with  cisplatin  at  the dosage  of  ≥  50mg/m2 as  monotherapy  or  in  combinations.  The validation  process  involved  known-group  validity,  discriminant validity, convergent validity and factor analysis. About 203 subjects who  were  diagnosed  with  cancer  were  recruited  in  this  study.  Theknown-group  validity  test  showed  that  there  were  no  significant differences  of  SF-36  domains  among  different  diagnosa.  All  of  the questions  met  the  criteria  of  convergent  validity  except  for  the questions  number  26,  28,  30  and  32.  Furthermore,  the  questions number 2  and  28  did  not meet  the  criteria  of discriminant  validity. This  study  presents  that  many  questions  are  needed  to  be reconstructed,  due  to  the  result  of  factor  analysis  which  showed that  those  questions  are  loaded  significantly  with  other  domain’s questions.  The  development  of  Indonesian  version  of  SF-36  scales in cancer disease is still less unstatisfactory. According to the result of this study, future study with new construction of questions in this version is still necessary.Key words: validation, SF-36, Indonesia, cancer